Matematică
hakanandrei21
2015-11-15 23:58:30
Te rog ajuta ma si pe mine si te voi rasplati cu o coroana! a=(1+2+.....+1994):1995; b=(2^17x4^8)^1995:8^665. Calculati: 2(a+b)-1
Răspunsuri la întrebare
cRsBatranu
2015-11-16 06:12:42

a = (1+2+...+1994) : 1995 = 1994 * 1995 : 2 : 1995 = 1994 : 2 * 1995 : 1995 = 1994 : 2 = 997 [latex]b=(2^{17}:4^8)^{1995}:8^{665} \ \ =[2^{17}:(2^2)^8]^{1995}:(2^3)^{665} \ \ =(2^{17}:2^{16})^{1995}:2^{1995} \ \ =2^{1995}:2^{1995} \ \ =1[/latex] 2(a+b)-1 = 2*998-1 = 1995

Adăugați un răspuns